Fabrication of the Soft Magnet using the Mixture of BaFe12O19 - Al2O3 at different Sintering Temperature - ginting, masno; Hia, Taufik Hidayat; N, Nasruddin M; Sebayang, Perdamean (LIPI Press, 2016)
Barium Hexaferrite (BaFe12O19) magnet has been made by adding Al2O3 using metallurgical powder method.Al2O3 with different composition such as 0, 40, 50 and 60 (% weight) was added to Barium Hexaferrite (BaFe12O19),and then sintered at temperatures of 900, 950, 1,000, 1,050, and 1,1000C and each sintering was hold for two hours.From the experiment it is found that some of Al2O3 reacts with BaFe12O19 and results in one new phase of FeAl2O3.Meanwhile, the morphology of the sample is found relatively homogeneous with the rod type particle size whichis less than 1 ?m. The best sample was obtained at 1,1000C sintering temperature, which gives the value of bulkdensity 4.34 g/cm3, porosity 21.98%, and flux density 72.95 Gauss.